2009
DOI: 10.1021/ma9001325
|View full text |Cite
|
Sign up to set email alerts
|

Necking Instability during Polydomain−Monodomain Transition in a Smectic Main-Chain Elastomer

Abstract: The mechanical response and the evolution of director orientation are characterized in a smectic, main-chain liquid crystalline elastomer (LCE) as it undergoes the familiar polydomain−monodomain (P−M) transition. Under uniaxial tension, the LCE behaves like an ordinary rubber-like network at low strains, and local director rotations are shown to slightly favor the perpendicular (“anomalous”) orientation of chain axes with respect to the draw direction. As strain increases, a well-defined yield stress is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 45 publications
(104 reference statements)
3
38
1
Order By: Relevance
“…Several previous communications have reported the soft plateau region [5,12,13] and necking [10,11] during PM transformations, but have only used the mechanical response from the nominal stress (s n ¼ F/A 0 ) in nonequilibrium conditions. The present results use true stress (s t ¼ s n Á l) versus strain (l), and are thus closer to reality and to the existent theories.…”
Section: Mechanical Properties Of a Polydomainmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous communications have reported the soft plateau region [5,12,13] and necking [10,11] during PM transformations, but have only used the mechanical response from the nominal stress (s n ¼ F/A 0 ) in nonequilibrium conditions. The present results use true stress (s t ¼ s n Á l) versus strain (l), and are thus closer to reality and to the existent theories.…”
Section: Mechanical Properties Of a Polydomainmentioning
confidence: 99%
“…[10] Other studies showed the mechanical behaviour of SmC MCLCEs as function of the crosslinking density, where the necking effect appeared at high degrees of crosslinking, while a soft plateau region was observed for low crosslinked elastomers. [11,12] Recently, the PM transition in a smectic-C A (SmC A ) MCLCE was attributed to the change in the polymer backbone conformation from hairpinned to fully extended.…”
Section: Introductionmentioning
confidence: 96%
“…There are, however, recent reports of slow, anelastic strain recovery in liquid crystalline networks (LCNs) [7][8][9][10][11][12][13][14][15] leading to what has been described by some as shape memory behavior [7-9, 12, 13]. Since it is anelasticity, rather than fast reversing elasticity, of these lightly crosslinked networks, that is, essential for strain retention in these materials; we prefer to refer to them as LCNs rather than as LCEs in this context [15].…”
mentioning
confidence: 99%
“…After cooling to room temperature, the mixture was poured into 1000 mL cold water and acidified with 6 N sulfuric acid. The precipitates were recrystallized in alcohol, isolated by filtration, and dried in a vacuum oven to obtain white crystals of 3-(4-(undec-10-enoyloxy)phenyl)acrylic acid (1) The intermediate 1 (33.0 g, 0.10 mol), 120 mL thionyl chloride, and 1.0 mL of pyridine were added into a round flask. The mixture was stirred at room temperature for 3 h, then heated to 60°C, and kept for 6 h in a water bath to ensure that the reaction finished.…”
Section: Synthesis Of the Lc Monomersmentioning
confidence: 99%
“…They have been developed as promising functional materials due to their remarkable properties such as interesting mechanical, electrical, and optical properties originating from rubber elasticity [1][2][3]. In addition, the orientation of the mesogens can be controlled through mechanical stress as well as by electric and magnetic fields.…”
Section: Introductionmentioning
confidence: 99%